ANALISIS KELAYAKAN USAHA PIA DENGAN PENDEKATAN KEUNTUNGAN PADA UKM PUTRA KUSUMA DI KECAMATAN SIPATANA KOTA GORONTALO - Vera Waty Adam; Irwan Bempah; Wawan K Tolinggi (Universitas Negeri Gorontalo, 2017)
Pia business feasibility analysis is conducted to assist SMEs kusuma son to see the feasibility of pia business so feasible to be developed. This research aims to analyze: 1) production cost structure of pia business in Ukm Putra Kusuma, 2) business income of pia in Ukm Putra Kusuma, 3) Feasibility of pia business in ukm kusuma son. This research was conducted at Kecamatan Sipatana Kota Gorontalo, from september until november 2017. The method used in this survey is survey method. The data collected includes secondary data and primary data. Primary data were obtained by direct interviews with employees while secondary data were obtained from books and BPS. Analysis of data used is the analysis include the cost structure of pia business production, business income pia, pia business feasibility in SMEs kusuma son in Kecamatan Sipatana City Gorontalo. The results showed that the production cost structure of business per month with fixed costs Average of Rp. 2.980.000 Monthly variable cost Average Rp. 10.760.000, the average value per month from the income of pia business is Rp. 25,000,000. while net income per month pia business in SMEs kusuma son is Rp. 11.260 million. the feasibility of pia business in SMEs Putra Kusuma street Kecamatan Sipatana City Gorontalo can be said worthy to be cultivated With the value of R/C ratio 1,81.